The Alberta Moving Beyond Breast Cancer (AMBER) Cohort Study: Recruitment, Baseline Assessment, and Description of the First 500 Participants. Issue 1 (December 2016) - Courneya, Kerry; McNeely, Margaret; Culos-Reed, S.; Vallance, Jeff; Bell, Gordon; Mackey, John; Matthews, Charles; Morielli, Andria; Cook, Diane; MacLaughlin, Sarah; Farris, Megan; Voaklander, Stephanie; et al.
Abstract Background To our knowledge, the Alberta Moving Beyond Breast Cancer (AMBER) Study is the first and only prospective cohort study of breast cancer survivors that includes objectively-measured physical activity (PA), sedentary behavior, health-related fitness (HRF), and biologic mechanisms focused on understanding breast cancer outcomes. The purpose of the present study was to report on the feasibility of recruitment, baseline measurement completion, and the representativeness of the first 500 participants. Methods AMBER is enrolling newly diagnosed stage I (≥T1c) to IIIc breast cancer survivors in Alberta, Canada. Baseline assessments are completed soon after diagnosis and include cardiorespiratory fitness, musculoskeletal fitness, body composition, objective and self-reported PA and sedentary behavior, lymphedema, and blood collection. Results Between July 2012 and November 2014, AMBER recruited its first 500 participants from a pool of 1, 447 (35 %) eligible breast cancer survivors. Baseline HRF assessments were completed on ≥85 % of participants with the exception of upper body strength. Collection of ≥4 days/week of monitoring for the Actigraph GT3X® and ActivPAL® were obtained from 90 % of participants. Completion rates were also high for blood (99 %), lymphedema (98 %), and questionnaires (95 %) including patient-reported outcomes and correlates of exercise. The first 500 participants in AMBER are an average age of 56 years, 60 % are overweight or obese, and 58 % have disease stage II or III. Conclusion Despite the modest recruitment rate and younger age, AMBER has demonstrated that many newly diagnosed breast cancer survivors are willing and able to complete a wide array of sophisticated and physically demanding HRF and PA assessments soon after diagnosis. AMBER is a unique breast cancer survivor cohort that may inform future randomized controlled trials on lifestyle and breast cancer outcomes as well as PA behavior change in breast cancer survivors. Moreover, AMBER may also inform guidelines on PA, sedentary behavior, and HRF for improving breast cancer outcomes and survivorship.